Ethics and the acquisition of organs - Wilkinson, T. M., 1968- (Oxford : Oxford University Press, 2011)
Transplantation is a medically successful and cost-effective way to treat people whose organs have failed - but not enough organs are available to meet demand. Wilkinson explores the ethical problems raised by policies for acquiring organs. Key topics include the rights of the dead, the role of the family, and the sale of organs.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 21, 2012).
Includes bibliographical references and index.
Keywords: Procurement of organs, tissues, etc. -- Moral and ethical aspects